2006
DOI: 10.1093/eurheartj/ehm020
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of high-dose atorvastatin compared with regular dose simvastatin

Abstract: In the prevention of cardiovascular events among patients with a previous MI, high-dose atorvastatin appears to be a cost-effective strategy when compared with generic simvastatin 20-40 mg in Denmark, Norway, and Sweden. In Finland, it is cost-effective in high-risk patients. The key driver of the cost-effectiveness is the price-difference between 80 mg atorvastatin and generic simvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…The validity of this model is confirmed by a comparable estimation of costs and health outcomes in previous studies assessing the cost‐effectiveness of intensive LLT for all versus standard LLT for all 11, 12, 13, 14, 15. Also, we based our assumptions on recent peer‐reviewed literature and adjusted event probabilities and risk of death for the age and cardiovascular history of patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The validity of this model is confirmed by a comparable estimation of costs and health outcomes in previous studies assessing the cost‐effectiveness of intensive LLT for all versus standard LLT for all 11, 12, 13, 14, 15. Also, we based our assumptions on recent peer‐reviewed literature and adjusted event probabilities and risk of death for the age and cardiovascular history of patients.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown that treating all patients with stable CAD with intensive LLT is a cost‐effective strategy 11, 12, 13, 14, 15. The costs and effects of treating patients with the highest predicted absolute benefit intensively and those with smaller benefit with standard therapy are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the model has been published (10). All patients start in the 'at risk' state.…”
Section: Methods Study Descriptionmentioning
confidence: 99%
“…Over the median follow-up of 4.8 years, mean LDL-C levels decreased from 3.15 mmol/L (121.5 mg/dL) at baseline to 2.69 mmol/L (104 mg/dL) for patients allocated simvastatin, and to 2.10 mmol/L (81 mg/dL) for patients allocated atorvastatin. Patients randomly assigned to high-dose atorvastatin experienced fewer major coronary events, defined as coronary death, nonfatal acute MI or cardiac arrest with resuscitation (hazard ratio [HR] An economic evaluation based on data collected during the IDEAL trial indicated that intensive lipid lowering with atorvastatin 80 mg would be cost-effective compared with treatment with generic simvastatin in Denmark, Norway and Sweden (10). In Finland, this strategy was found to be cost-effective in high-risk patients (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation